Graphene‐Stabilized Silver Nanoparticle Electrochemical Electrode for Actuator Design. (26th November 2012) - Lu, Luhua; Liu, Jinghai; Hu, Ying; Zhang, Yuewei; Chen, Wei
<x xml:space="preserve">Abstract</x> An electrochemical actuator based on a graphene‐stabilized silver‐nanoparticle (AgNP) electrode is presented. Owing to the actuation characteristics — persistence, fast strain rate, and wide frequency response — the strategy of hybridizing reduced graphene oxide (RGO) and AgNPs is believed to be of great value for developing more RGO/metal hybrid–based electrochemical actuators or sensors for various applications. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>